G219(P) Transport risk index of physiologic stability score in neonatal transport. (May 2019) - Kulkarni, A; Chavan, A; Kaul, S; Balan, S
Abstract : Introduction: High risk pregnant women are generally referred to a tertiary care centre for delivery but sometimes critically ill neonates delivered elsewhere require transfer to a higher center, requiring skilled transport team and equipment. Stability during transport is essential and there are few tools available to assess the outcome of neonatal transport. This prospective study was conducted to determine the usefulness of transport risk index of physiologic stability (TRIPS) score for predicting key neonatal transport outcomes in a tertiary care centre. Method: TRIPS SCORE was developed and validated by Lee SK et al in 2001. It is a practical, empirically weighted and physiology based system for assessment of neonatal transport outcomes. TRIPS comprises of 4 items namely, temperature, blood pressure, respiratory status and response to noxious stimuli. The present study was conducted in a level III Neonatal Unit which routinely retrieves sick babies. Total 116 transported neonates who fulfilled the inclusion criteria were included in the study. One member of transport team recorded TRIPS Score within 15 min on arrival at the referring hospital and again immediately after arrival at our NICU. Depending upon the pre transport TRIPS Score, we stratified neonates in to 5 categories of increasing TRIPS score (0–10, 11–20, 21–30, 31–40 and >40). For each category we separated the neonates in to 3 groups: Post transport TRIPS Post transport TRIPS = pre transport TRIPS Post transport TRIPS >pre transport TRIPS Result: The 7 day mortality was directly proportional to TRIPS score and it was significantly higher for the score above 40. Similarly as the score increased to 40 and above, chances of IVH, shock and sepsis increased significantly. For each pre transport TRIPS category, decrease in TRIPS score after transport was associated with lower mortality than if the TRIPS score were unchanged, where as an increase in TRIPS score after transport was associated with a higher mortality. Similar findings were observed in case of sepsis, shock and IVH. Conclusion: Our study concludes that TRIPS is a useful instrument in predicting key neonatal transport outcomes.